Apartheid Politics in South Africa - Okuma Lelo (International Journal of Science and Society, 2020)
Racial discrimination is a very big problem and is found in several countries such as the United States, Britain and the most dominant in South Africa with Apartheid politics. Therefore, South Africa is the focus of the fight against racism towards the realization of justice. The word Apartheid means "separation" in African language and it describes the racial rigidity that governs the division between the white minority population and the majority white population. The struggle of the majority of black Africans against the dominance of white minorities is the main and final racial conflict. The international community actively encourages it. However, the white group was quite a lot and was too strong while the black power was so weak and divided, that in the end a person named Nelson Mandela would appear who was active in fighting for the elimination of Apartheid politics in South Africa, on the grounds that racial crises and conflicts would arise. what happened there was soon over and South Africa became a conducive country.